2003
DOI: 10.1145/948383.948410
|View full text |Cite
|
Sign up to set email alerts
|

The OptIPuter

Abstract: This architecture/infrastructure of parallel optical networks couples data exploration, visualizationy and ' •• collaboration technologies through IP at multi-gigabit speeds. he OptlPuter exploits a new world of distributed Grid infrastructure in which the ' central architectural element is optical networking, not computers, creating "supernetworks," or networks faster than te the computers attached to them. As in supercomputing a decade ago, parallelism makes this transition possible. But this time, paralleli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
59
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(59 citation statements)
references
References 5 publications
0
59
0
Order By: Relevance
“…These include the Scalable Adaptive Graphics Environment (SAGE) [9] based on TeraVision [22] and TeraScope [31], OptiStore [30], Active Data Repository [11], Active Semantic Caching [4], DataCutter [5], ParVox [12], The Remote Interactive Visualization and Analysis System (RIVA) [13], OptiPuter [23], Digital Light Table [10] and Scalable Parallel Visual Networking [7]. However, these systems do not support remote compute resources nor the ability to customize personal computers on-the-fly to become compute nodes in the system.…”
Section: Introductionmentioning
confidence: 99%
“…These include the Scalable Adaptive Graphics Environment (SAGE) [9] based on TeraVision [22] and TeraScope [31], OptiStore [30], Active Data Repository [11], Active Semantic Caching [4], DataCutter [5], ParVox [12], The Remote Interactive Visualization and Analysis System (RIVA) [13], OptiPuter [23], Digital Light Table [10] and Scalable Parallel Visual Networking [7]. However, these systems do not support remote compute resources nor the ability to customize personal computers on-the-fly to become compute nodes in the system.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts to create wide area network (WAN) environments in which bounds on communication delay jitter are significantly smaller than those in most segments of the current Internet, started appearing only in recent years. The OptIPuter research sponsored by the National Science Foundation (NSF) is a good example [13].…”
Section: Introductionmentioning
confidence: 99%
“…The optIPuter project [10] observed that network speeds have been outstripping the ability of processor speeds to keep up. This technology inversion resulted in the emergence of LambdaGrids, which have fundamentally changed the way that we think about distributed computing.…”
Section: Introductionmentioning
confidence: 99%